Multi-response calibration and validation of a DEM for wet Mactra veneriformis–mudflat sediment mixtures during mechanised harvesting - Hangqi Li; Gang Mu; Bin Xu; Guangcong Chen; Guochen Zhang; Xiuchen Li (Biosystems Engineering, 2026)

Ship emissions amplify soluble iron in PM2.5 in a typical coastal port in North China - Yiqi Chen; Wei Tan; Yuan Fang; Qi Yuan; Yujue Wang; Weiwei Guan; Minkang Zhi; Xiaohuan Liu; Liang Xu; Jian Zhang; Guochen Wang; Xiaohong Yao; et al. (Environmental Pollution, 2026)

Data-Driven Insights and Prediction of Bauxite-Hosted Lithium Mineralization - Xiaokang Liang; Guotao Sun; Yong Fu; Bo Tang; Peiwen Chen; Zaiping Shi; Shijiang Yang; Guochen Zhou; Zhonghong Huang; Qiaolin Fu; Tianyi Liu (Natural Resources Research, 2026)

Constructed wetland substrate–mediated stereoselective transformation of metolachlor: Influence of redox conditions and microbial community dynamics - Liangjin Chen; Yucong Zheng; Mawuli Dzakpasu; Qian Yang; Guochen Liu; Liping Zhao; Tianfu Wu; Dongfu Zhang; Xiaochang Wang; Rong Chen (Environmental Research, 2026)

Wollastonite improves soybean yield without toxic trace elements enrichment - Yanzhi Wang; Ji Chen; Guochen Li; Chao Gong; Ang Wang; Ronghua Kang; Feifei Zhu; Jiaoyue Wang; Chang Liu; Dong Liu; Chenxia Su; Quanping Zhang; et al. (Nutrient Cycling in Agroecosystems, 2025)

Scalable, durable MOF@PEI-based nanofiber membrane for efficient synergistic removal of Cr(VI) in wastewater - Jun Gao; Ze Mao; Dengbing Wang; Yuan Chen; Hanlei Lin; Jiongsheng Song; Dingsheng Wu; Shen Li; Guochen Bian; Zhenyu Li; Quan Feng (Journal of Environmental Chemical Engineering, 2025)

Organic nitrates in coastal aerosols: Seasonal dynamics, influencing factors, and formation pathways - Mengke Tian; Zhijian Ding; Jia Chen; Juntao Huo; Guochen Wang; Jian Xu; Hao Li; Ziwei Liu; Yunkai Wang; Nan Ye; Xiaofei Qin; Yanfen Lin; et al. (Atmospheric Environment, 2025)

Exploring the decentralized blue-green infrastructure network layouts for urban flood risk management - Guochen Hu; Yu Zhang; Chenyu Chen; Zhou Shen; Yifan Hu; Haiwei Yin; Zhongyang Shao; Huan Zheng; Furong Chen (Landscape and Ecological Engineering, 2025)

Mechanical Characterization and Dual-Layer Discrete Element Modeling of Mactra veneriformis - Bin Xu; Yazhou Yang; Hangqi Li; Guangcong Chen; Yizhi Chang; Feihong Guo; Hao Wu; Jixuan Zhao; Zijing Liu; Guochen Zhang; Xiuchen Li; Hanbing Zhang; et al. (Fishes, 2025)
The discrete element model of Mactra veneriformis currently employs an oversimplified multi-sphere approach using EDEM’s Hertz–Mindlin model, assuming uniform shell–flesh mechanical properties. This study developed an advanced dual-layer flexible bonding model through comprehensive biomechanical testing. Mechanical properties and shell morphology were experimentally characterized to inform model development. Parameter optimization combined free-fall experiments with Plackett–Burman screening, steepest ascent method, and Box–Behnken RSM, yielding optimal contact parameters: flesh–flesh stiffness (X1) = 3.64 × 1011 N/m3, shell–flesh interface (X3) = 1.48×1013 N/m3, shell–shell tangential stiffness (X6) = 3.23 × 1012 N/m3, and normal strength (X7) = 8.35 × 106 Pa. Validation showed only 4.89% deviation between simulated and actual drop tests, with hydraulic impact tests confirming excellent model accuracy. The developed model accurately predicts mechanical behavior and shell fracture patterns during harvesting operations. This research provides a validated numerical tool for optimizing clam cultivation and harvesting equipment design, offering significant potential to reduce shell damage while improving harvesting efficiency in bivalve aquaculture systems.

Smart UAV-assisted blueberry maturity monitoring with Mamba-based computer vision - Fan Zhao; Yinyin He; Jian Song; Jiaqi Wang; Dianhan Xi; Xinlei Shao; Qingyang Wu; Yongying Liu; Yijia Chen; Guochen Zhang; Chenyu Zhang; Yulun Chen; et al. (Precision Agriculture, 2025)
Purpose Precise segmentation of blueberry maturity is critical for optimizing harvestschedules and maintaining product quality. Traditional methods, which rely on manualinspection, are not only labor-intensive but also cost-inefficient. This study presents a novelframework that integrates deep learning-based super-resolution reconstruction (SRR) withsemantic segmentation to provide a fast and accurate solution for maturity assessment. Methods The SRR module enhances image resolution, enabling more detailed feature extraction.Semantic segmentation models—incorporating convolutional neural networks (CNNs),Transformer-based models, and the Mamba-based state space architecture—further improvesegmentation precision. Results Experimental results indicate that the MambaIR modelachieves a structural similarity index measure (SSIM) of 82.26% in SRR tasks, while the Mamba-based segmentation model attains a mean Intersection over Union (mIoU) of 83.15%. Conclusion By uniting SRR and semantic segmentation, our framework not only advances thetechnical accuracy of maturity detection but also holds strong potential for real-time, cost-effective deployment in precision agriculture systems, supporting intelligent decision-making at scale.

A robust black carbon prediction model derived from observational datasets in the Yangtze River Delta region, China - Lian Duan; Pak Lun Fung; Qingyan Fu; Jia Chen; Juntao Huo; Kan Huang; Guochen Wang; Martha Arbayani Zaidan; Zhigang Guo; Tareq Hussein (Environmental Pollution, 2025)

Seafloor debris detection using underwater images and deep learning-driven image restoration: A case study from Koh Tao, Thailand - Fan Zhao; Baoxi Huang; Jiaqi Wang; Xinlei Shao; Qingyang Wu; Dianhan Xi; Yongying Liu; Yijia Chen; Guochen Zhang; Zhiyan Ren; Jundong Chen; Katsunori Mizuno (Marine Pollution Bulletin, 2025)

Enhanced rock weathering boosts ecosystem multifunctionality via improving microbial networks complexity in a tropical forest plantation - Xing Wang; Guochen Li; Arshad Ali; Camelia Algora; Manuel Delgado-Baquerizo; Daniel S. Goll; Sara Vicca; Tongtong Xu; Boyuan Bi; Qiong Chen; Luxiang Lin; Yunting Fang; et al. (Journal of Environmental Management, 2025)

Transient HR enhancement by RAD51-stimulatory compound confers protection on intestinal rather than hematopoietic tissue against irradiation in mice - Zhiyu Lu; Dong Chen; Ning Zhang; Zhiyuan Zheng; Zimo Zhou; Guochen Liu; Jiawei An; Yong Wang; Yongping Su; Wensheng Chen; Fengchao Wang (DNA Repair, 2024)

Multi-process atmospheric particle number size distribution over the Bohai Sea: Insights from cruise and onboard unmanned aerial vehicle observations - Ziwei Liu; Hao Li; Jie Tang; Mian Wang; Haitao Zheng; Tao Luo; Xiaoquan Song; Chengfeng Liu; Guochen Wang; Xiaofei Qin; Jia Chen; Da Lu; et al. (Atmospheric Environment, 2024)

Species composition and distribution of common Crassostrea and Saccostrea oysters along the coast of Hainan Island - Ruijing Lu; Ya Chen; Peizhen Ma; Cui Li; Zhen Zhang; Guochen Zang; Zhenqiang Liu; Haiyan Wang (Journal of Oceanology and Limnology, 2024)

Enhanced silicate weathering accelerates forest carbon sequestration by stimulating the soil mineral carbon pump - Tongtong Xu; Zuoqiang Yuan; Sara Vicca; Daniel S. Goll; Guochen Li; Luxiang Lin; Hui Chen; Boyuan Bi; Qiong Chen; Chenlu Li; Xing Wang; Chao Wang; et al. (Global Change Biology, 2024)
Enhanced silicate rock weathering (ERW) is an emerging strategy for carbon dioxide removal (CDR) from the atmosphere to mitigate anthropogenic climate change. ERW aims at promoting soil inorganic carbon sequestration by accelerating geochemical weathering processes. Theoretically, ERW may also impact soil organic carbon (SOC), the largest carbon pool in terrestrial ecosystems, but experimental evidence for this is largely lacking. Here, we conducted a 2‐year field experiment in tropical rubber plantations in the southeast of China to evaluate the effects of wollastonite powder additions (0, 0.25, and 0.5 kg m −2 ) on both soil organic and inorganic carbon at 0–10 cm depth. We found that ERW significantly increased the concentration of SOC and HCO 3 − , but the increases in SOC were four and eight times higher than that of HCO 3 − with low‐ and high‐level wollastonite applications. ERW had positive effects on the accrual of organic carbon in mineral‐associated organic matter (MAOM) and macroaggregate fractions, but not on particulate organic matter. Path analysis suggested that ERW increased MAOM mainly by increasing the release of Ca, Si, and Fe, and to a lesser extent by stimulating root growth and microbial‐derived carbon inputs. Our study indicates that ERW with wollastonite can promote SOC sequestration in stable MOAM in surface soils through both the soil mineral carbon pump and microbial carbon pump. These effects may have been larger than the inorganic CDR during our experiment. We argue it is essential to account for the responses of SOC in the assessments of CDR by ERW.

Design and synthesis of low-potential and cycling-stable cobalt dicarboxylate bipyridine complexes for high-voltage aqueous organic redox flow batteries - Bin Liu; Wei Wei; Yu Wang; Manrong Song; Youke Chen; Honglin Chen; Liuping Chen; Qiuxia Dai; Shengxin Yao; Junhui Xu; Guochen Jia; Tianshou Zhao (Science Bulletin, 2024)

Enhanced rock weathering increased soil phosphorus availability and altered root phosphorus‐acquisition strategies - Boyuan Bi; Guochen Li; Daniel S. Goll; Luxiang Lin; Hui Chen; Tongtong Xu; Qiong Chen; Chenlu Li; Xing Wang; Zhanqing Hao; Yunting Fang; Zuoqiang Yuan; et al. (Global Change Biology, 2024)
Enhanced rock weathering (ERW) has been proposed as a measure to enhance the carbon (C)‐sequestration potential and fertility of soils. The effects of this practice on the soil phosphorus (P) pools and the general mechanisms affecting microbial P cycling, as well as plant P uptake are not well understood. Here, the impact of ERW on soil P availability and microbial P cycling functional groups and root P‐acquisition traits were explored through a 2‐year wollastonite field addition experiment in a tropical rubber plantation. The results show that ERW significantly increased soil microbial carbon‐use efficiency and total P concentrations and indirectly increased soil P availability by enhancing organic P mobilization and mineralization of rhizosheath carboxylates and phosphatase, respectively. Also, ERW stimulated the activities of P‐solubilizing ( gcd , ppa and ppx ) and mineralizing enzymes ( phoADN and phnAPHLFXIM ), thus contributing to the inorganic P solubilization and organic P mineralization. Accompanying the increase in soil P availability, the P‐acquisition strategy of the rubber fine roots changed from do‐it‐yourself acquisition by roots to dependence on mycorrhizal collaboration and the release of root exudates. In addition, the direct effects of ERW on root P‐acquisition traits (such as root diameter, specific root length, and mycorrhizal colonization rate) may also be related to changes in the pattern of belowground carbon investments in plants. Our study provides a new insight that ERW increases carbon‐sequestration potential and P availability in tropical forests and profoundly affects belowground plant resource‐use strategies.

Wollastonite powder application increases rice yield and CO2 sequestration in a paddy field in Northeast China - Fangna Wang; Feifei Zhu; Deze Liu; Yuying Qu; Dong Liu; Jin Xie; Ang Wang; Ronghua Kang; Zhi Quan; Yinghua Li; Xin Chen; Guochen Li; et al. (Plant and Soil, 2024)

Atmospheric saccharides over the East China Sea: Assessment of the contribution of sea-land emission and the aging of levoglucosan - Mengxin Fu; Hao Li; Lan Wang; Mengke Tian; Xiaofei Qin; Xuan Zou; Cheng Chen; Guochen Wang; Congrui Deng; Kan Huang (Science of The Total Environment, 2023)

Unveiling the pollution and risk of atmospheric (gaseous and particulate) polycyclic aromatic hydrocarbons (PAHs) in a heavily polluted Chinese city: A multi-site observation research - Tao Wang; Luyao Zhang; Pei Zhang; Guangyuan Yu; Chong Chen; Xiaofei Qin; Guochen Wang; Xiansheng Liu; Rui Li; Liwu Zhang; Zhonghuan Xia (Journal of Cleaner Production, 2023)

Seasonal differences in continental outflows and marine emissions of organic aerosols in the East China Sea: Insight from the variation of saccharides - Hao Li; Lan Wang; Xiaofei Qin; Guochen Wang; Mengxin Fu; Cheng Chen; Jian Xu; Congrui Deng; Kan Huang (Atmospheric Research, 2023)

Relationship between light absorption properties of black carbon and aerosol origin at a background coastal site - Haiyan Li; Chengfeng Liu; Hao Li; Guochen Wang; Xiaofei Qin; Jia Chen; Yanfen Lin; Juntao Huo; Qingyan Fu; Yusen Duan; Congrui Deng; Kan Huang (Science of The Total Environment, 2023)

Improved prediction of chlorophyll-a concentrations in reservoirs by GRU neural network based on particle swarm algorithm optimized variational modal decomposition - Xihai Zhang; Xianghui Chen; Guochen Zheng; Guangli Cao (Environmental Research, 2023)

Efficiency of sulfamethoxazole removal from wastewater using aerobic granular sludge: influence of environmental factors - Di Cui; Zeyi Chen; Ximing Cheng; Guochen Zheng; Yuan Sun; Hongna Deng; Wenlan Li (Biodegradation, 2021)

Predicting the near-field strong ground motion based on uncertainties in asperities: an opportunity to reproduce the characteristics of the 1970 Tonghai earthquake (Ms 7.8) - Zongchao Li; Jize Sun; Xueliang Chen; Guochen Wang; Qingfeng Ding (Journal of Seismology, 2021)

Fatty acid composition of Camellia oleifera oil - Jinlin Ma; Hang Ye; Yukui Rui; Guochen Chen; Naiyan Zhang (Journal of Consumer Protection and Food Safety, 2011)